Successful Control of Disseminated Intravascular Coagulation by Recombinant Thrombomodulin during Arsenic Trioxide Treatment in Relapsed Patient with Acute Promyelocytic Leukemia - Motohiro Shindo; Katsuya Ikuta; Lynda Addo; Satoshi Ito; Mikihiro Fujiya; Yoshihiro Torimoto; Yutaka Kohgo (Case Reports in Hematology)
Disseminated intravascular coagulation (DIC) frequently occurs in patients with acute promyelocytic leukemia (APL). With the induction of therapy in APL using all-trans retinoic acid (ATRA), DIC can be controlled in most cases as ATRA usually shows immediate improvement of the APL. However, arsenic trioxide (ATO) which has been used for the treatment of relapse in APL patients has shown to take time to suppress APL cells, therefore the control of DIC in APL with ATO treatment is a major problem. Recently, the recombinant soluble thrombomodulin fragment has received a lot of attention as the novel drug for the treatment of DIC with high efficacy. Here, we present a relapsed patient with APL in whom DIC was successfully and safely controlled by rTM during treatment with ATO.